Pathogens in animal meal and the use of Salmex (R) in the elimination of Clostridium perfringens - Cardozo, M. V. [UNESP]; Schocken-Iturrino, R. P. [UNESP]; Beraldo-Massoli, M. C. [UNESP]; Cavani, R. [UNESP]; Casagrande, M. F. [UNESP]; Boarini, L. [UNESP]; Borges, C. A. [UNESP]; Beraldo, L. G. [UNESP] (Academic Journals, 2012)
The microbiological quality of the ingredients used in feed production is extremely important for animal and public health because food can transmit pathogens. Chemical additives, such as Salmex (R), may be used to control these pathogens, since many sporulated microorganisms are resistant to conventional heat treatment. For these reasons, through the conventional bacteriological methods, this study evaluated the presence of pathogens in animal meal and tests the efficiency of additives to combat highly resistant microorganisms. Of the 180 samples of meal analyzed, 71 (39.4%) were positive for the presence of Clostridium perfringens, and 41 (22.8%) were positive for the presence of Salmonella spp. The additive tested, Salmex (R), was effective in eliminating C. perfringens, with significantly decreased bacterial counts 24 h after treatment and total absence of C. perfringens after five days of treatment in all the samples tested. The presence of the pathogens Salmonella spp. and C. perfringens in animal meal endanger both the public and animal health. The efficiency of Salmex (R) in eliminating C. perfringens is a major breakthrough for the poultry industry.
Keywords: Poultry; microbiology; public health; animal health